The effectiveness of music–movement integration for vulnerable groups: a systematic literature review - Juntunen, Marja-Leena; Sutela, Katja (Frontiers in Psychology, 2023)
This systematic review synthesized the outcomes of previous intervention studies published from January 2000–October 2022 to evaluate the effectiveness of Dalcroze-based or similar music–movement integration among groups of individuals considered vulnerable (in relation to their abilities and health/wellbeing). The target groups addressed in previous intervention studies included individuals with special educational needs (such as disorders, disabilities, or impairments) or with a (risk of) decline in health and/or physical strength. Twenty articles met the review inclusion criteria. All studies showed beneficial outcomes for music–movement intervention except one that suffered from low adherence rates. In older adults, the benefits were cognitive, physical, social, and/or emotional, including improved postural stability, balance, gait safety, confidence in mobility, metamemory skills, dual-task performance, social and physical pleasure, autotelic/flow experience, enjoyment, health, and quality of life. In individuals with special educational needs, improvement was seen in relation to inclusion, reductions in compulsive and other problematic behaviors, self-regulation, perceptual and cognitive abilities and functions, linguistic and learning skills, auditory attention and phonological awareness, social interaction, engagement, and agency.